The short and long-term effects of a lifestyle intervention in children with mental illnesses: a randomized controlled trial (Movementss study) - Emilie M. A. van Tetering; Jet B. Muskens; Jeroen Deenik; Sigrid Pillen; Wiepke Cahn; Inès von Rosenstiel; Mieke Oomen; Nanda N. Rommelse; Wouter G. Staal; Helen Klip (BMC Psychiatry, 2023)
Abstract Background A lifestyle including poor diet, physical inactivity, excessive gaming and inadequate sleep hygiene is frequently seen among Dutch children. These lifestyle behaviors can cause long-term health problems later in life. Unhealthy lifestyle and poor physical health are even more prevalent among children with mental illness (MI) such as autism, attention-deficit/hyperactivity disorder, depression, and anxiety. However, research on lifestyle interventions among children with MI is lacking. As a result, there are currently no guidelines, or treatment programs where children with MI and poor lifestyle can receive effective support. To address these issues and to provide insight into the effectiveness of lifestyle interventions in children with MI and their families, the Movementss study was designed. This paper describes the rationale, study design, and methods of an ongoing randomized controlled trial (RCT) comparing the short-term (12 weeks) and long-term (1 year) effects of a lifestyle intervention with care as usual (CAU) in children with MI and an unhealthy lifestyle. Methods A total of 80 children (6–12 years) with MI according to DSM-V and an unhealthy lifestyle are randomized to the lifestyle intervention group or CAU at a specialized child and adolescent mental hospital. The primary outcome measure is quality of life measured with the KIDSCREEN. Secondary outcomes include emotional and behavior symptoms, lifestyle parameters regarding diet, physical activity, sleep, and screen time, cognitive assessment (intelligence and executive functions), physical measurements (e.g., BMI), parenting styles, and family functioning, prior beliefs, adherence, satisfaction, and cost-effectiveness. Assessments will take place at the start of the study (T0), after 12 weeks (T1), six months (T2), and 12 months of baseline (T3) to measure long-term effects. Discussion This RCT will likely contribute to the currently lacking knowledge on lifestyle interventions in children with MI. Trial registration trialsearch.who.int/ NL9822. Registered at November 2nd, 2021.